Strategies of Islamic Education Teachers Based on Local Wisdom in Enhancing Learning Quality at Madrasah: Strategi Guru Pendidikan Agama Islam Berbasis Kearifan Lokal dalam Meningkatkan Kualitas Pembelajaran di Madrasah - Khosi'in, Imam; Wiarsih, Nur; Faishol, Riza; Baharun, Hasan (STAI Ma'had Aly Al-Hikam Malang, 2024)
This research analyzes strategies of islamic education teachers based on local wisdom in enhancing learning quality in Madrasah Tsanawiyah Negeri (MTsN) 6 Banyuwangi. This research uses a qualitative case study type approach. The research subjects included the Head of the Madrasah, Deputy Head of Curriculum, Deputy Head of Student Affairs, PAI Teachers, Religious Figures, local cultural figures, and students. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The research results show that PAI teachers who integrate local wisdom values into the curriculum and teaching methods can increase student engagement and motivation. Effective strategies include using learning materials that contain local culture, developing extracurricular activities that focus on local traditions, and collaborating with local communities to provide contextual learning experiences. Applying local wisdom in PAI learning increases students' understanding of religious material and strengthens their cultural identity, ultimately improving the quality of education in madrasas. This research suggests that PAI curriculum development should pay more attention to local wisdom as an integral part of learning strategies to achieve more holistic and meaningful educational outcomes. Artikel ini menganalisis strategi guru Pendidikan Agama Islam (PAI) berbasis kearifan lokal dalam meningkatkan kualitas pembelajaran di Madrasah Tsanawiyah Negeri (MTsN) 6 Banyuwangi. Artikel ini menggunakan pendekatan kualitatif dan jenis penelitian studi kasus. Subjek penelitian meliputi Kepala Madrasah, Wakil Kepala Madrasah Bidang Kurikulum, Wakil Kepala Madrasah Bidang Bidang Kesiswaan, Guru PAI, Tokoh Agama, Tokoh Budaya, dan Siswa. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru PAI yang mengintegrasikan nilai-nilai kearifan lokal ke dalam kurikulum dan metode pengajaran, dapat meningkatkan keterlibatan dan motivasi siswa. Strategi yang efektif antara lain dengan menggunakan materi pembelajaran yang memuat budaya lokal, mengembangkan kegiatan ekstrakurikuler yang fokus pada tradisi lokal, dan berkolaborasi dengan komunitas lokal untuk memberikan pengalaman belajar yang kontekstual. Penerapan kearifan lokal dalam pembelajaran PAI meningkatkan pemahaman siswa terhadap materi keagamaan dan memperkuat identitas budayanya, yang pada akhirnya meningkatkan mutu pendidikan di madrasah. Artikel ini menyarankan agar pengembangan kurikulum PAI sebaiknya lebih memperhatikan kearifan lokal sebagai bagian integral dari strategi pembelajaran untuk mencapai hasil pendidikan yang lebih holistik dan bermakna. Kata Kunci: Local wisdom; Learning Quality; Contextual Learning Experiences.